HUBUNGAN SIKAP PENJAMAH MAKANAN DENGAN CARA PRODUKSI PANGAN YANG BAIK PADA INDUSTRI RUMAH TANGGA PANGAN DI KAMPUNG KUE SURABAYA[Correlation of Food Handlers Attitude with Good Manufacturing Practice in the Household Food Industry in Kampung Kue Surabaya] - Maya Amelia; Annis Adi (Universitas Airlangga, 2019)
The application of Good Manufacturing Practice (GMP) can improve quality of products. Good manufacturing practice aim to make a safe product to be consumed. Attitude of food handlers can affect practice of food handlers on production process. The purpose of this study was to analyze the correlation between attitude of food handlers with GMP. This research was an observational study, using cross sectional design. Subjects were 38 food handlers, taken by simple random sampling. Data were collected include interview method using attitude questionnaires and observation of the GMP. Data were analyzed using Spearman Correlation. Results showed majority of food handlers have adequate attitude (55.3%), meanwhile GMP were poor (89.5%). There was a signifi cant correlation between attitude (p=0.018) with good manufacturing practice. Food handlers have to pay more attention on the cleanliness of production space and the use of appropriate clothes for handling the food, such as apron, cap, and masker. Food handlers who have had food safety certifi cate needs to share GMP to other food handlers. Periodically training in food safety needs to be done at Kampung Kue Surabaya.